FAILURES IN AUDITS AND MEDICAL BOARDS IN THE EVALUATION FOR SPINE SURGERY AUTHORIZATION IN BRAZIL - RODRIGO ANTONIO ROCHA DA CRUZ ADRY (Coluna/Columna)
ABSTRACT Objective: The audit and medical board in surgeries focuses on the evaluation and adequacy of surgical procedures. The objective was to compare whether the evaluations were in line with the resolutions of the Federal Council of Medicine (CFM) and the standards of the National Health Agency (ANS) in conducting audits for the release of spinal surgical procedures. Methods: The research was conducted through document analysis of the results of audits and medical boards for the evaluation and release of surgical procedures in neurosurgery and spinal surgery. Results: A total of 55 audits were evaluated. The most frequent failures on the part of the audit were the denial of material in 49 audits (89.09%) and the denial of procedure in 46 audits (83.63%), which effectively vetoed the procedure. Conclusion: The failures identified in the audits and medical boards of surgeries can compromise the impartiality and quality of the audit process. These failures can lead to an increase in complaints from health insurance companies to other regulatory agencies. Level of Evidence IV; Economic and Decision Analysis.